Variação dos sinais vitais e predição de desfechos negativos em pacientes hospitalizados com COVID-19 - Cruz, Nayara Cristina Romão (Universidade Federal de São Carlos, 2023)
Introduction: The Sars-Cov-2 virus is capable of affecting several systems of the human body, with heterogeneous, unpredictable and not fully understood clinical presentation and health outcomes. Vital signs translate the clinical status of patients and are easily accessible information, routinely obtained in clinical practice as clinical flags. However, it is not known whether the variation of these signs during the course of COVID-19 has predictive potential for negative outcomes. Objective: To analyze the variation of vital signs during the first 48h of patients hospitalized by COVID-19 and to verify their ability to predict negative health outcomes. Method: Retrospective observational cohort study involving 121 adult patients diagnosed with COVID-19 admitted between March 2020 and June 2021 in the ICU/ward sectors. Clinical information was collected (age, gender, BMI); previous comorbidities; symptoms on admission; length of hospitalization; oxygen use and flow on admission. Regarding vital signs, the following were collected: temperature; heart rate (HR); systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) and oxygen pulse saturation (SpO2), considering for analysis of the variation; standard deviation (SD), coefficient of variation (CV) and amplitude (max-min) during the first 48h of hospitalization. Patients were classified according to health outcomes into: negative outcomes (death and need for orotracheal intubation) and positive outcomes (hospital discharge). Results: 18 (14.8%) patients had negative outcomes and were older (65.06 ± 9.67 vs 53.02 ± 15.41 years), hypertensive (66.6% vs 33.0%) and had cardiovascular disease (33.3% vs 12.6%). Patients with negative outcomes showed higher HR variation (SD:7.93 ± 4.95 vs 5.26 ± 4.40; CV:9.05 ± 5.01 vs 6.44 ± 5.39; amp: 11.17 ± 6.98 vs 7.47 ± 6.25) and MAP (6.32 ± 2.95 vs 4.48 ± 4.10; CV: 7.03 ± 3.66 vs 4.79 ± 4.26; amp: 8.94 ± 4.18 vs 6.33 ± 5.80) compared to the group with positive outcomes. The area under the curve (AUC) was 0.68 (95% CI 0.56;0.80, p<0.05) for HR variability variables (SD, CV and amplitude) and 0.69 (95% CI 0.56;0.82, p<0.05) for MAP variation variables (SD, CV and amplitude). Conclusion: higher HR and MAP variation during the first 48h of hospitalization may be related to negative health outcomes in patients hospitalized by COVID-19
Variation of vital signs and prediction of negative outcomes in patients hospitalized with COVID-19
Keywords: COVID-19; Sinais vitais; Sistema cardiovascular; Sistema respiratório; Hospitalização; Vital signs; Cardiovascular system; Respiratory system; Hospitalization; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL